A first note on the excavations at UAQ38, a new Neolithic site in the Emirate of Umm al‐Quwain. (10th October 2019) - Degli Esposti, Michele; Borgi, Federico; Gallou, Claire; Martin, Chloë; Lidour, Kevin; Méry, Sophie
Abstract: At the end of 2018, the first season of excavation was carried out at the shell midden site of UAQ38. The site occupies the top of a sand dune not far from UAQ36 and UAQ2, two other recently investigated Neolithic shell middens. Several well‐stratified anthropogenic levels were excavated at UAQ38, which can be dated mainly to the 5th millennium BC, although the recorded artefacts suggest a possible older date for the lowest levels. Food waste, post‐holes, fireplaces, and burnt shell dumpings attest to human activities that took place at the site over a rather long period of time. Here the stratigraphic sequence will be presented, together with a first overview of the artefactual assemblage. The collected data will be concisely discussed in order to fit the site within the typology of Neolithic settlements that can be proposed for the area. UAQ38 is so far the only Neolithic site along the northeastern coast of the UAE for which stratified charcoal is available for dating.